UNLOCKING THE POTENTIAL ECONOMIC IN UNDEVELOPED REGENCY THROUGH MARITIME INFRASTRUCTURE - ABDULGANI, Imanuddin (PPI Dunia, 2018)
The North Kayong Regency is one of the new Regency in West Kalimantan Province that is still lack of infrastructure development such as infrastructure and public amenities. The purpose of this research is to contribute in regional development planning policy through determine appropriate method in maritime infrastructure for increasing regional economic growth. Our study shows that the best practice to improve the development planning process is improve better and appropriate policies that might be apply through the new methods on practice oriented, focus on strategies, tools and manage the utilization of planning and resources. By maintain strategies, develop solution that integrates different dimension of regional planning and resources in every conceivable way to solve the problem and to overcome the obstacles.